2020
DOI: 10.17796/1053-4625-44.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changes in the Occlusion and Occlusal Vertical Dimension in Children Following the Placement of Preformed Metal Crowns Using the Hall Technique

Abstract: Objectives: To evaluate the time taken and the mechanism through which the occlusion settles following the placement of a preformed metal crown (PMC) using the Hall technique. The secondary objective was to assess any temporo mandibular joint dysfunction (TMD) resulting from the Hall technique through a questionnaire. Study Design: 44 children fulfilling the inclusion criteria were evaluated for changes in overbite and occlusal vertical dimension (OVD) following the placement of preformed metal crowns (PMCs) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 5 publications
4
24
0
1
Order By: Relevance
“…This compensation may occur due to the intrusion of the restored molar and its antagonist, the eruption of other teeth, or the combination of both 28 . It is also important to note that in this study there was no significant difference with respect to TMJ pain in the group treated with SSC (Table 5), corroborating the findings of Joseph et al, which showed that children treated with the Hall technique did not develop TMJ symptomatology 29 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This compensation may occur due to the intrusion of the restored molar and its antagonist, the eruption of other teeth, or the combination of both 28 . It is also important to note that in this study there was no significant difference with respect to TMJ pain in the group treated with SSC (Table 5), corroborating the findings of Joseph et al, which showed that children treated with the Hall technique did not develop TMJ symptomatology 29 …”
Section: Discussionsupporting
confidence: 88%
“…This difference may not be clinically significant if the patients are considered to be in mixed dentition, and during this period, physiological changes occur due to the development of the occlusion. Other studies have reported that with the placement of SSC with the Hall technique, the vertical dimension is re‐established in a period of four weeks 29,30 . This compensation may occur due to the intrusion of the restored molar and its antagonist, the eruption of other teeth, or the combination of both 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study showed that after two weeks of applying the Hall's crown technique to the lower primary molars, 27% of cases (30% for the first molar and 23% for the second molar) had a bilateral balanced occlusion, while about 25% of the cases (20% For the first molar and 30% for the second molar) needed up to three weeks to obtain a bilateral balanced occlusion, and 35% of cases required about a month to obtain abilateral balanced occlusion. We noted that after a month of application, 87% of cases (84% for the first molar and 90% for the molar the second) have returned to the position of a balanced occlusion bilaterally and the remaining cases of 13% (17% for the first molar and 10% for the second molar) took more than a month, achiev-ing a balanced occlusion upon examination after two months, which is consistent with most of the previous studies that also found that the Occlusal Vertical Dimension returned to a balanced state about a month after application [18,20,21].…”
Section: Discussionsupporting
confidence: 90%
“…The increased OVD can be compensated by the intrusion of the restored tooth and its antagonist, continued re-eruption of other teeth in the arch, or a combination of both. Rose Maria et al also reported that any changes in occlusion following the SSC placement could settle in four weeks [ 20 ]. Increased OVD exposes the periodontal ligament of the restored tooth to increased bite force, resulting in blood flow disturbance in the compressed periodontal ligament (PDL), followed by cell death, called hyalinization, which is resorbed by macrophages, with resorption of the undermined bone through osteoclast activity, eventually leading to tooth movement to settle OVD.…”
Section: Discussionmentioning
confidence: 99%